2008
DOI: 10.2746/042516408x293565
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffects of hydrochloric and lactic acids on bioelectric properties of equine gastric squamous mucosa

Abstract: HCl induced alteration in bioelectric properties of equine NG mucosa whereas addition of LRS did not, other than those changes seen with HCl alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
0
18
0
2
Order By: Relevance
“…The fasting time and type and feeding scheme may have influenced these results. In vitro studies have demonstrated that VFA has minimal ulcerogenic capacity in the non-glandular mucosa of the horse (21). The effect of lactic acid is dependent on the amount and time of exposure to the mucosa; therefore, it is possible to infer that this VFA plays a poor role in the generation of gastric ulcers in the horses of this study.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The fasting time and type and feeding scheme may have influenced these results. In vitro studies have demonstrated that VFA has minimal ulcerogenic capacity in the non-glandular mucosa of the horse (21). The effect of lactic acid is dependent on the amount and time of exposure to the mucosa; therefore, it is possible to infer that this VFA plays a poor role in the generation of gastric ulcers in the horses of this study.…”
Section: Discussionmentioning
confidence: 83%
“…This results in different levels of change in the cell membrane permeability, according to the type of acid (5,6,21). Acetic acid showed the highest concentration (59%) in the gastric contents of the horses of this study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such risk factors may lead to an imbalance in aggressive factors within the stomach such as hydrochloric acid, pepsin, volatile fatty acids and bile acids, and those factors protecting against gastric ulceration such as mucus and bicarbonate (Andrews et al, 2008). Gastric ulcers in the squamous mucosa may be directly related to Burden, Gallagher, Thiemann and Trawford the amount of exposure to gastric acidity whereas ulceration in the glandular area of the stomach is more likely to be due to decreased blood flow, bicarbonate and mucus secretion.…”
Section: Discussionmentioning
confidence: 99%